Family firms in transition : case studies on succession, inheritance, and governance - Carsrud, Alan L. (SpringerBriefs in Business, 2012)
Many of the challenges faced by family-owned businesses develop after the firm has reached a stage of maturity, when the first generation is faced with issues concerning the role of their children in the business and the long-term future of the enterprise.  This collection of case studies from around the world demonstrates  how governance of both the business and the family (or lack thereof)  impacts succession of leadership in the firm and the inheritance of ownership and wealth. It is the role of governance and how it impacts both family and firm that link these family business cases together with succession and inheritance.  These topics have been clustered together because the social systems of the family and the management system of the firm have significant impacts on the success, or failure, of succession plans.  All the planning in the world for succession and inheritance will not succeed if the firm does not have a well established and functional governance system.  Likewise, if the family does not understand its role in the governance of the firm and the mechanisms for making sound decisions, succession choices may not be accepted by family members.  Most family firms fail because of succession issues, not economic ones. This volume features nine in-depth cases of family-owned business from a variety of industries to illuminate the dynamics of governance, succession, and inheritance.  Each case illustrates the complexity of issues and, through interactive exercises and questions, offers readers approaches to solutions, which may include less-than-optimal compromises or even selling the business as the only viable option.    The examples and insights will prove valuable for students and members of entrepreneurial and family-owned firms, as well as consultants, investors, and other professional advisors.